Principals' Leadership Strategies in Conflict Management in Islamic Boarding Schools - Azzahra, Azzahra; Anugrah, Ruri Liana (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to describe and evaluate the principal's leadership strategies in conflict management at the Hayatuddiyar Islamic Boarding School Pekanbaru, as well as to identify the supporting and inhibiting factors. The study employs a descriptive-evaluative qualitative approach, with data collected through in-depth interviews with five informants—consisting of the principal, teachers, educational staff, and female students—complemented by observation and documentation. The results indicate that the leadership strategies implemented include strengthening open communication through a "normalizing mandatory reporting" policy, participatory decision-making based on deliberation (musyawarah), and delegation of authority according to standard operating procedures. Furthermore, the principal applies mediation and tabayyun mechanisms, personal approaches, post-conflict evaluation, moral guidance (character building), educational sanctions, and the ishlah process for character restoration. Evaluatively, these strategies are considered effective in resolving conflicts constructively and maintaining justice. The primary supporting factors are stakeholder cooperation and effective communication, while identified inhibitors include miscommunication caused by personal closeness exceeding professional boundaries, protracted conflicts, students' closed character, dishonesty, and external environmental influences. This study concludes that adaptive leadership based on Islamic boarding school values is capable of creating harmonious organizational stability.